Answer:
i edgggg g t g h tr fe erfg bh hnhy r hrh r r t hth
Step-by-step explanation:
Answer:
2
Step-by-step explanation:
The coefficient is the number in front of the variable.
So, in this case, the coefficient of n^2 is 6 and of n is 2.
ANSWER
![f(x) = (x + 3)^{2} - 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x%20%20%2B%20%203%29%5E%7B2%7D%20%20-%201)
EXPLANATION
The vertex of the graph is at
![(-3,-1)](https://tex.z-dn.net/?f=%28-3%2C-1%29)
The equation of the graph in vertex form is given by the formula,
![f(x) = a{(x - h)}^{2} + k](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20a%7B%28x%20-%20h%29%7D%5E%7B2%7D%20%20%2B%20k)
The above graph has a minimum point, hence
![a > \: 0](https://tex.z-dn.net/?f=a%20%3E%20%20%5C%3A%200)
When we put these values into the equation we obtain,
![f(x) = a(x - - 3)^{2} + - 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%20a%28x%20-%20%20-%203%29%5E%7B2%7D%20%20%20%2B%20%20-%201)
This implies that,
![f(x) = a(x + 3)^{2} - 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%20a%28x%20%20%2B%20%203%29%5E%7B2%7D%20-%201)
The point (-2,0) lies on the line.
![a( - 2 + 3)^{2} - 1 = 0](https://tex.z-dn.net/?f=a%28%20-%202%20%2B%203%29%5E%7B2%7D%20%20%20%20-%201%20%3D%200)
![a = 1](https://tex.z-dn.net/?f=a%20%3D%201)
![f(x) = (x + 3)^{2} - 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%28x%20%20%2B%203%29%5E%7B2%7D%20%20-%201)
The correct answer is D.
Answer:
Step-by-step explanation:
x+y=a
a=x+y
x−y=b
b=x−y
Good luck honey!